“When my Moods Drive Upward There Is Nothing I Can Do about It”: A Review of Extreme Appraisals of Internal States and the Bipolar Spectrum - Kelly, Rebecca E.; Dodd, Alyson L.; Mansell, Warren (Frontiers in Psychology, 2017)
The integrative cognitive model provides a comprehensive account of bipolar disorder that, if empirically-supported, has important potential implications for psychological therapies. This article is the first to review the evidence for this model. We evaluate the evidence (up to 2017) for four hypotheses derived uniquely from the model: extreme positive and negative appraisals of internal states are associated with (1) risk of developing bipolar disorder; (2) bipolar disorder diagnosis; (3) relevant clinical and functional outcomes including hypomanic and depressive mood symptoms; and (4) outcomes over time. Research involving individuals with diagnosed mood disorders as well as non-clinical populations is reviewed. The hypotheses were broadly supported and several consistent findings were not accounted for by alternative psychological models of bipolar disorder. The evidence base is limited by a relative paucity of prospective studies; only 6 of the 31 studies identified. Implications for theory, research and clinical practice are discussed.